PENGARUH GAYA BELAJAR MODEL DAVID KOLB TERHADAP KEMAMPUAN AFEKSI SISWA PADA MATA PELAJARAN AL-QURAN HADITS (Pascasarjana IAIN Kudus, 2013)
Improving student affection abilities needs effective learningdesign. By David Kolb’s learning style models, this study aimedto determine the effect of the use of the ability of affective learningstyles of students. Data revealed by questionnaire with 75respondents at MTs Nurul Ulum Tanjunganyar. The results showedthat the use of learning styles David Kolb positive effect on students’affective skills, evidenced by Freg value 16.946 is greater than theF table for a significance level of 1% and 5% (7.00 3.97). Regression equation formed is Y = 85,825 + 0,526 X. Results showed the calculation of the coefficient of determination 0.188 or 18.8%, indicated that 18.8% of students level of affection influencedthe use of student learning styles.